2021
DOI: 10.1097/ftd.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Point-of-Care Testing with Enzyme-Multiplied Immunoassay Technique and Liquid Chromatography Combined With Tandem Mass Spectrometry Methods for Therapeutic Drug Monitoring of Mycophenolic Acid: A Preliminary Study

Abstract: Background: For mycophenolic acid (MPA), therapeutic drug monitoring is an essential tool for dosage optimization in transplant recipients and autoimmune diseases. In China, a new commercial kit using an immunochromatographic assay (FICA) with a point-of-care testing system was approved for therapeutic drug monitoring of MPA. However, corroboration between FICA and clinically used assays remains unknown. The authors evaluated MPA concentrations in heart transplant recipients obtained by FICA, highperformance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to compare the concentration of VPA measured by LC–ESI-MS/MS and EMIT methods with a large number of samples. The results of this study demonstrated the overestimation by routine EMIT assay compared with LC–ESI-MS/MS, which was in line with previous reports for other medications ( Prémaud et al, 2004 ; Li et al, 2017 ; Zhou et al, 2020 ). In the current study, 782 plasma samples from 711 pediatric patients submitted to our lab for routine EMIT assay for VPA monitoring were enrolled.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first study to compare the concentration of VPA measured by LC–ESI-MS/MS and EMIT methods with a large number of samples. The results of this study demonstrated the overestimation by routine EMIT assay compared with LC–ESI-MS/MS, which was in line with previous reports for other medications ( Prémaud et al, 2004 ; Li et al, 2017 ; Zhou et al, 2020 ). In the current study, 782 plasma samples from 711 pediatric patients submitted to our lab for routine EMIT assay for VPA monitoring were enrolled.…”
Section: Discussionsupporting
confidence: 92%
“…However, the entire procedure is time-consuming, usually taking approximately 3 h to obtain the first drug concentration result. However, the subsequent analyses are significantly faster, with a turnaround time of approximately 2–3 min/sample [ 19 ]. However, owing to the irregular arrival of clinical specimens, UPLC-MS/MS is not suitable for routine clinical monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, an alternative determination method that is simple, rapid, and user-friendly is required. The EMIT method is a commercially available analytical technique that is widely used for routine therapeutic drug monitoring of immunosuppressants [ 19 , 20 ] and anti-seizure drugs [ 21 ]. The EMIT approach is simple to execute and requires only ordinary laboratory equipment and no sophisticated equipment.…”
Section: Discussionmentioning
confidence: 99%
“…There are various methods for the quantification of MPA and MPAG levels. These include immunassays, HPLC linked to an ultraviolet detector (HPLC/UV) and HPLC linked to a tandem mass spectrometer (HPLC‐MS/MS) (Danafar & Hamidi, 2015; Glahn‐Martinez et al., 2018; Kikuchi et al., 2018; Klepacki et al., 2012; Kunicki et al., 2015; Liu et al., 2021; Seyfinejad & Jouyban, 2021; Zhou et al., 2021). LC‐MS/MS is the most commonly used method for the quantification of MPA followed by immunoassays (College of American Pathologists Surveys, 2022).…”
Section: Commentarymentioning
confidence: 99%
“…LC‐MS/MS is the most commonly used method for the quantification of MPA followed by immunoassays (College of American Pathologists Surveys, 2022). However, immunoassays are prone to interferences from MPA metabolites and may overestimate MPA concentrations (De Nicolo et al., 2020; Kikuchi et al., 2018; Zhou et al., 2021). This could be a serious problem in renal failure, in which MPA metabolites accumulate to significantly high concentrations.…”
Section: Commentarymentioning
confidence: 99%